(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of this study was to develop a low-cost kit for the detection of subclinical mastitis (SCM) and to check its validity, reproducibility, and efficacy at the field level. Materials and Methods: A total of 550 quarter milk samples from crossbred dairy cows were collected, of which 400 milk samples were used to validate the newly developed BLRI mastitis test (BMT) kit to justify its efficacy as an individual test kit in detecting SCM based on somatic cell count (SCC) by direct microscopic count (DMC). The efficacy of the newly developed BMT was compared with the California Mastitis Test (CMT) kit. Another 150 milk samples were subjected to SCC determined by DMC and DCC (De Laval cell counter®) categorized by CMT and BMT scores. Results: A SCM test kit, namely, BMT kit was successfully developed in this study. The percentage accuracy of CMT and BMT were 76.75% and 75.75%; sensitivity 69.36% and 67.56%; specificity 85.95% and 85.85%; positive predictive value 86.03% and 85.71%; negative predictive value 69.23% and 68%, respectively. A p value of 0.001 was found for both CMT and BMT. However, CMT and BMT had no significant difference in sensitivity (p = 0.778). Average SCCs (cells/ml) determined by DCC and DMC, respectively, were mostly corresponded to the SCC ranges of both CMT and BMT scores. Conclusion: The newly developed BMT kit is an independent, cheap, farmer-friendly, first country made, and reliable SCM diagnostic test kit that can be used at field condition. J. Adv. Vet. Anim. Res., 6(3): 425-430, September 2019